2006
DOI: 10.1002/rra.930
|View full text |Cite
|
Sign up to set email alerts
|

A new method to determine interstitial flow patterns in flume studies of sub‐aqueous gravel bedforms such as fish nests

Abstract: Flume studies often seek to measure and record the interstitial flow within plane-bed sediment bodies and within sediment beds with wavy surfaces, such as those typified by salmonid fish spawning nests and river-dunes. A simple, inexpensive method is described to record and map, at discrete points, the spatial variation in interstitial flow speeds in experimental fine gravel beds. The procedure uses activated carbon granules to capture a tracer: Rhodamine WT dye. Calibration of the uptake of dye by the carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
6
16
0
Order By: Relevance
“…Similarly, shrimp mounds, mussel clusters, and crabs induce pressure variations and hyporheic circulation in ocean environments (Huettel and Gust 1992; Ziebis et al. 1996), while salmon and trout nests do the same in riverine and lacustrine environments (Carling et al. 2006; Tonina 2005).…”
Section: Mechanics Of Hyporheic Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, shrimp mounds, mussel clusters, and crabs induce pressure variations and hyporheic circulation in ocean environments (Huettel and Gust 1992; Ziebis et al. 1996), while salmon and trout nests do the same in riverine and lacustrine environments (Carling et al. 2006; Tonina 2005).…”
Section: Mechanics Of Hyporheic Exchangementioning
confidence: 99%
“…For example, White (1990) proposed that hyporheic circulation is developed below beaver dams, lamprey nests, and Chara hummocks (macrophytic algae), each of which modify bed topography, local pressure distributions, and nutrient fluxes (White and Hendricks 2000). Similarly, shrimp mounds, mussel clusters, and crabs induce pressure variations and hyporheic circulation in ocean environments (Huettel and Gust 1992;Ziebis et al 1996), while salmon and trout nests do the same in riverine and lacustrine environments (Carling et al 2006;Tonina 2005). In general, hyporheic circulation caused by aquatic organisms enhances subsurface velocity and the flow of oxygen and nutrients in ways that are beneficial to the organism or its progeny (Tonina 2005;White 1990;White and Hendricks 2000).…”
Section: Energy Head (Total Streambed Pressure)mentioning
confidence: 99%
“…The majority of studies examining interstitial flow velocity in salmonid redds at c . 30 cm depth observed values below the maximum used in this study: most observed velocities were well below 1·0 cm s −1 (Greig et al ., ; Zimmermann & Lapointe, ; Carling et al ., ). Malcolm et al .…”
Section: Discussionmentioning
confidence: 99%
“…Such interstitial flow velocities recorded in the MRSHEP reach fell within the range of those observed in other salmonid-supporting rivers. Many have observed interstitial velocities well below 1·0 cm s −1 (Greig et al ., 2005;Zimmermann & Lapointe, 2005;Carling et al ., 2006). Malcolm et al .…”
Section: E R C E D R I V E R F I E L D M E a S U R E M E N T Smentioning
confidence: 99%
“…They manifest themselves in the increased incidence of extreme hydrological events (floods which affects not only the river channel morphology but also the ecological state of rivers [WYŻGA et. al 2012a, b; and stream flow droughts which that is also due to situation when in the gravel of the river bed one can expect more water than in the river channel [CARLING et al 2006]). For example, the research associated with the occurrence of a flood risk on the Kielce agglomeration area revealed, that in the highly urbanized Silnica catchment (as a result of flows which occur on average once every 100 years), the flood area will be nearly 150 hectares and will cover heavily invested areas .…”
Section: Introductionmentioning
confidence: 97%